BENTUK TUTUR BAHASA MANDAILING DALAM MAKKOBAR PADA PROSESI PERNIKAHAN DI KECAMATAN RANAH BATAHAN - Silpia Nami; Reva Lina Tiawati; Silvia Marni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the speech forms of the Mandailing language used in the Makkobar tradition during wedding ceremonies in Ranah Batahan District and to analyze the functions of the speech acts realized in customary interactions. The research employed a qualitative descriptive approach. The data consisted of oral utterances collected through non-participant observation, audio recording, and field notes, with traditional leaders and Makkobar participants as data sources. The analysis was grounded in speech act theory, covering locutionary, illocutionary, and perlocutionary acts. The findings reveal that Makkobar discourse is predominantly characterized by informative locutionary acts and various illocutionary functions, including assertive, directive, commissive, expressive, and declarative acts. Word choice, intonation, and politeness strategies are influenced by social status, age, customary roles, and kinship relations. Furthermore, the study identifies the impact of linguistic acculturation with Minangkabau and Indonesian, resulting in variations in speech patterns without diminishing Mandailing politeness values. The Makkobar tradition plays a crucial role as a medium for preserving language, social norms, and the cultural identity of the Mandailing community in a diaspora context.